STEAM Education and the Innovative Pedagogies in the Intelligence Era - Zhan, Zehui; Hu, Qintai; Wang, Shan; Liu, Xuan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This academic reprint is a timely and essential resource for educators, researchers, and policymakers seeking to revolutionize STEAM education. As we embark on the era of intelligence, technologies such as Artificial Intelligence (AI) and the Internet of Things (IoT) offer unique possibilities to improve learning experiences in Science, Technology, Engineering, Arts, and Mathematics. However, there is a notable gap in the research on how to effectively integrate these innovations and foster critical skills for the 21st century. Comprising 12 groundbreaking papers, this Special Issue addresses the urgent need for transformative teaching and learning methods that blend intelligent technologies with cutting-edge pedagogies in STEAM education. The reprint showcases original research and reviews that provide valuable insights into the current landscape of STEAM education and innovative approaches in this intelligence-driven age. This collection is designed to inspire further exploration, collaboration, and advancement in the field, ultimately benefiting future generations through the enhancement of STEAM education. Perfect for anyone interested in the future of education, this reprint is your guide to unlocking the potential of intelligent technologies and innovative pedagogies for a new era of learning.